POLA PENGGUNAAN DAN ANALISIS EFEKTIVITAS BIAYA OBAT ANTINYERI PADA PASIEN DIABETIK NEUROPATI DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Sari, Tri Purma; Perwitasari, Dyah Aryani; Supadmi, Woro (Jurnal Riset Kefarmasian Indonesia, 2023)
Diabetic neuropathy is gathering symptom clinic which influence system nerves, well single or combination and could happen in a manner suddenly, no detected, with symptom clinic and no specific signs but dangerous. Incidence diabetic neuropathy happen between 60% to 70% on type I and type II DM patients. Methods of data collection carried out prospectively. Data were obtained from outpatient data with a diagnosis of diabetic neuropathy who met the inclusion criteria and received analgetics from September to December 2020. Then a cost-effectiveness analysis was performed by calculating the ACER (Average Cost-Effectiveness Ratio) and ICER (Incremental Cost-Effectiveness Ratio) values. The results showed that the most commonly used analgetics was gabapentin at 65.96%, either alone or in combination with an effectiveness percentage of 83.87%. The use of analgetics with the lowest cost is a single Paracetamol of IDR 73,770. The lowest ACER values were shown in the use of the single analgetics Paracetamol and the combination of Amitriptyline-Paracetamol, namely 737.70 and 805.30.